testWhere1 = a
             where b = 1                
                      a = b+1

> testWhere1
 2

testWhere2 = a
             where b = 1
                      c = 1/(b - b)                   
                      a = b+1

> testWhere2
 2.0

The same thing happens with let.

testLet1 = let a = b+1 
                         b = 1             
               in a

> testLet1
2
             
testLet2 = let a = b+1 
                   c = 1/(b - b)
                   b = 1             
               in a
             
> testLet2
2.0



-- Russ Abbott
______________________________________
  Professor, Computer Science
  California State University, Los Angeles

  Google voice: 424-242-USA0 (last character is zero)
  blog: http://russabbott.blogspot.com/
  vita:  http://sites.google.com/site/russabbott/
______________________________________